ANALISA KARAKTERISTIK PASIR SUNGAI SEBAGAI BAHAN CETAKAN PADA PENGECORAN LOGAM - Nasution, irfan maulana; Yusuf, Muhammad (E-Journal Universitas Malikussaleh, 2023)
Casting is a process to make a component by pouring liquid metal into a sand mold. In the casting process, sand is the basic material used for making molds. Commonly used molding sands are mountain sand, beach sand, river sand and silica sand. Molding sand must have requirements such as formability, suitable permeability, good sand grain size distribution, resistance to high temperatures, suitable binder composition, and sand must be cheap. This study aims to determine the quality of krueng sawang river sand for molding materials in metal casting, for which several tests will be carried out including water content test, clay content test, sand grain size distribution test, grain shape examination and sand strength test. In this study, the method used is the experimental method and is a quantitative study that clearly describes the results of experiments in the laboratory on a number of test objects, then analyzes the data using numbers. The average water content is 12.50%. The average clay content is 3.36%. From the results of sand distribution testing, the results of sand distribution obtained a total percentage of 98.575%. Mountain sand grain fineness number data has a GFN value of 33.78. From the sand shape test, it can be seen that most of the sawang river sand grains are partially angular (Sub angular grain). The compressive strength test results show that the dry specimen value is higher than the wet specimen. Based on anova analysis with a percentage error of 0.05 on dry sand obtained f-count> f-table with an f-count value of 21.71138, f-table 4,066180557, p-value 0.000337 so it can be concluded that H1 is accepted and H0 is rejected. In the anova analysis on wet sand, f-count> f-table is obtained with an f-count value of 14.51971, f-table 4, 066180557, p-value 0.001335, so it can be concluded that H1 is accepted and H0 is rejected. While the anova analysis on the distribution of printed sand grain distribution values is obtained by f-count> f-table with the value of f-count 164.8742, f-table 2.620654148, p-value 9.16E-18 so it can be concluded that H1 is accepted and H0 is rejected.